Sugar-Sweetened Beverage Intake as Risk Factor for Pre-Metabolic Syndrome in Adult Women - Anggraini, Wiriesta; Probosari, Enny; Panunggal, Binar (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2019)
This study aimed to analyse the correlation between sugar-sweetened beverage (SSB) intake and pre-metabolic syndrome in adult women. This was a case-control study involving 46 subjects of adult women 40-55 years old in each group. SSB intake and nutrients intake data were obtained through Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) then analysed with NutriSurvey. Statistical analysis done was Chi-Square test. The result showed that case group had an average of waist circumference was 91.9±8.9 cm with a minimum of 80 cm and a maximum of 110 cm. Triglyceride levels in blood had average 166.8±14.4 g/dl with a minimum of 150 g/dl and a maximum of 197 g/dl in case group. The average intake of SSB in pre-metabolic syndrome (case group) was 41.5±1.7 g with minimum and maximum of intake was 12 g and 92.6 g respectively. There was a significant correlation between SSB intake and pre-metabolic syndrome in adult women p<0.05 (OR=3.56; 95% CI:1.243-10.170).